Prospects of the bionic approach in architecture and environmental design (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
This article examines the contemporary challenges taking place in the fields of architecture and environmental design as they emerged as being under biodesign, and explores the prospective scope of the bionic approach. The advancement of science and technology brings new requirements and challenges that give rise to new dimensions of professional and artistic collaboration between architects and designers, green architecture, and the formation of new environmental spaces. It defines as well the significant role of bio-design in the context of technogenic society. There is also a great emphasis put on adopting a systemic view for the approach in the design of buildings that cater to environmental, social, demographic, and economic needs. This also introduces specific requirements for “green” architecture in this essay is approached through the lens of the modern practice of construction and design across the globe where bionic and “green architecture” ideas are imposed to foster an interdisciplinary way of working. This is to increase efficacy, comfort, and environmental friendliness of the architectural space, object design, setting, and even the ecological condition of space. The “green” architecture pointers have undergone an analysis and in-depth review of the bionic forms integrated into green architecture endeavors. New biodesign techniques and green innovations have been the primary language in the construction industry giving rise to superseding and increased precision in the architectural solutions and designs that utilize international standards.
Keywords: design; bionics; bionic forms; bio-design; an architectural environment; integrated approach in design